Neuroimaging and Neuropsychological Studies in Sports-Related Concussions in Adolescents: Current State and Future Directions - Narayana, Shalini; Charles, Christopher; Collins, Kassondra; Tsao, Jack W.; Stanfill, Ansley Grimes; Baughman, Brandon (Frontiers in Neurology, 2019)
Mild traumatic brain injury (mTBI), or concussion, is a serious neurological concern that many adolescent athletes will face during their athletic careers. In some instances, the effects of sports-related head injury are long-lasting. Due to their still-developing brains, adolescents appear to be more vulnerable to long-term repercussions of these injuries. In this review we will examine the pathophysiology of mTBI, its acute effects and long-term risks from sustaining injury, and current and needed advancements in the areas of neuropsychological testing, accelerometer telemetry, and neuroimaging. Current methods do not adequately measure the extent of an injury that an athlete may sustain, potentially putting these athletes at a much greater risk for long-term effects. To better understand mTBI, neuropsychological testing best practices need to be developed, standardized, and implemented based on sound scientific evidence in order to be propagated as clinical guidelines. Wearable accelerometers can be used to assess thresholds for mTBI and cumulative effects of concussive and subconcussive injuries. Novel neuroimaging methods that can detect anatomical abnormalities and functional deficits with more specificity and sensitivity should be developed. Young athletes are particularly a vulnerable population warranting immediate and significant research aimed at protecting them against sports related injury and mitigating their long-term deficits.